Coactivators and general transcription factors have two distinct dynamic populations dependent on transcription. (19th July 2017) - Vosnakis, Nikolaos; Koch, Marc; Scheer, Elisabeth; Kessler, Pascal; Mély, Yves; Didier, Pascal; Tora, László
Abstract: SAGA and ATAC are two distinct chromatin modifying co‐activator complexes with distinct enzymatic activities involved in RNA polymerase II (Pol II) transcription regulation. To investigate the mobility of co‐activator complexes and general transcription factors in live‐cell nuclei, we performed imaging experiments based on photobleaching. SAGA and ATAC, but also two general transcription factors (TFIID and TFIIB), were highly dynamic, exhibiting mainly transient associations with chromatin, contrary to Pol II, which formed more stable chromatin interactions. Fluorescence correlation spectroscopy analyses revealed that the mobile pool of the two co‐activators, as well as that of TFIID and TFIIB, can be subdivided into "fast" (free) and "slow" (chromatin‐interacting) populations. Inhibiting transcription elongation decreased H3K4 trimethylation and reduced the "slow" population of SAGA, ATAC, TFIIB and TFIID. In addition, inhibiting histone H3K4 trimethylation also reduced the "slow" populations of SAGA and ATAC. Thus, our results demonstrate that in the nuclei of live cells the equilibrium between fast and slow population of SAGA or ATAC complexes is regulated by active transcription via changes in the abundance of H3K4me3 on chromatin. Synopsis: Imaging of live cell nuclei reveals the existence of separate free and chromatin‐bound pools of co‐activator complexes SAGA and ATAC, with chromatin association regulated by H3K4 methylation levels. Live cell imaging reveals the mobility of co‐activator complexes (SAGA and ATAC) and general transcription factors (TFIID and TFIIB). SAGA, ATAC, TFIID and TFIIB are highly dynamic and mainly exhibit transient associations with chromatin. Fluorescence correlation spectroscopy show that mobile pools of SAGA, ATAC, TFIID and TFIIB can be subdivided into "fast" (free nuclear) and "slow" (chromatin‐interacting) populations. Active transcription‐dependent H3K4 trimethylation determines the ratio between fast and slow populations of SAGA or ATAC. Abstract : Imaging of live cell nuclei reveals the existence of separate free and chromatin‐bound pools of co‐activator complexes SAGA and ATAC, with chromatin association regulated by H3K4 methylation levels.